2018
DOI: 10.1155/2018/5425346
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Therapy Enhances Mitochondrial Delivery into Target Cells and Protects against Acute Respiratory Distress Syndrome

Abstract: This study tested the hypothesis that shock wave therapy (SW) enhances mitochondrial uptake into the lung epithelial and parenchymal cells to attenuate lung injury from acute respiratory distress syndrome (ARDS). ARDS was induced in rats through continuous inhalation of 100% oxygen for 48 h, while SW entailed application 0.15 mJ/mm2 for 200 impulses at 6 Hz per left/right lung field. In vitro and ex vivo studies showed that SW enhances mitochondrial uptake into lung epithelial and parenchyma cells (all p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…In this way, our findings, in addition to being consistent with the findings from previous studies, [45][46][47][48][49] could, once again, explain why the liver enzyme, fibrosis and liver injury score were markedly increased in IRI animals. Of importance was that melatonin-pretreated Mito therapy significantly suppressed inflammatory reaction, DNA damage, oxidative stress, cellular apoptosis and fibrosis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this way, our findings, in addition to being consistent with the findings from previous studies, [45][46][47][48][49] could, once again, explain why the liver enzyme, fibrosis and liver injury score were markedly increased in IRI animals. Of importance was that melatonin-pretreated Mito therapy significantly suppressed inflammatory reaction, DNA damage, oxidative stress, cellular apoptosis and fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Plentiful data have shown that exogenous mitochondrial transfusion not only effectively rescued the function and integrity of endogenous mitochondria but also refreshed the depleted mitochondria in organ, resulting in preserving the ischaemia-reperfusion-related organ dysfunction. 16,46 The most important finding in the present study was that melatonin-pretreated exogenous mitochondria not [45][46][47][48][49] Additionally, increased oxidative stress in circulation and intracellular/mitochondrial compartment notably down-regulated mitochondrial function and depleted energy-storage capacity. 16,46 An essential finding in the present study was that these above-mentioned parameters of molecular-cellular perturbations [45][46][47][48][49] were substantially increased in IRI animals as compared to SC animals.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations